2009
DOI: 10.1016/j.genhosppsych.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The management of depression during pregnancy: a report from the American Psychiatric Association and the American College of Obstetricians and Gynecologists

Abstract: Objective To address the maternal and neonatal risks of both depression and antidepressant exposure and develop algorithms for periconceptional and antenatal management. Method Representatives from the American Psychiatric Association, the American College of Obstetricians and Gynecologists and a consulting developmental pediatrician collaborated to review English language articles on fetal and neonatal outcomes associated with depression and antidepressant treatment during childbearing. Articles were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
318
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(329 citation statements)
references
References 58 publications
(58 reference statements)
5
318
2
4
Order By: Relevance
“…Clinical and preclinical data clearly point to a pervasive impact of SSRI exposure on development [11,59]. It is possible that perinatal exposure to SSRIs protects against the effects of maternal depression.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and preclinical data clearly point to a pervasive impact of SSRI exposure on development [11,59]. It is possible that perinatal exposure to SSRIs protects against the effects of maternal depression.…”
Section: Discussionmentioning
confidence: 99%
“…Women of childbearing age face a high risk of depression, and pregnancy can increase the risk of a depressive episode (Gaynes et al 2005). Between 14% and 23% of women will experience a depressive disorder while pregnant (Yonkers et al 2009), and depressive symptoms in a mother have been found to be associated with adverse reproductive outcomes in some studies, including low birth weight, shorter gestation, preterm delivery, increased risk for irritability and reduced activity and attentiveness (Yonkers et al 2009). Moreover, depression during pregnancy increases women's risk of postpartum depression (U.S. Department of Health & Human Services 2009), which can have consequences for both mother and child.…”
Section: Depression Health Behaviors Self-objectification and Pregmentioning
confidence: 99%
“…Although, a history of depression is an important risk fac- tor for depression during pregnancy but half of women with no previous history of depression at pregnancy are affected (27). Psychosocial approaches including individual and group psychotherapy can be used for treatment of the most of patients with mild to moderate depression and these approaches are rather than drug therapy (28). Therefore, the identification and screening of women with depression in pregnancy can help their treatment and support strategies.…”
Section: Discussionmentioning
confidence: 99%